Design and Implementation of a Python-Based Cinema Ticket Ordering Prototype Using Linear Search - Ramando Girsang; Hisyam Fadhila; Yunita Sartika sari; Nia Rahmah Kurnianda; Ifan Prihandi (Journal Collabits, 2026)
The increasing adoption of digital services has encouraged the development of ticketing systems that simplify access to movie information and transaction processes. This study aims to design and implement a Python-based cinema ticket ordering prototype and to examine the suitability of the Linear Search algorithm for movie-title lookup in a small and unsorted dataset. The development process consists of requirements analysis, system design, implementation, functional verification, and algorithmic complexity analysis. The prototype supports customer input, movie selection, ticket quantity calculation, optional food and beverage ordering, and transaction calculation. Linear Search is selected because it can operate directly on a small unsorted list without preprocessing or an additional indexing structure. Theoretical comparison shows that Linear Search has O(n) average and worst-case time complexity, while Binary Search offers O(log n) complexity for sorted data and hash-based lookup offers O(1) average lookup time with additional storage requirements. The study therefore does not claim Linear Search as a new or universally efficient algorithm. Its contribution lies in presenting a transparent small-scale ticket-ordering architecture and an academically justified algorithm selection. Future development should incorporate persistent database storage, a graphical or web/mobile interface, authentication, secure payment integration, usability evaluation, and empirical performance benchmarking.